2018
DOI: 10.1139/cjpp-2017-0596
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol treatment reversed left ventricular dysfunction in castrated male rats: an echocardiographic study

Abstract: No data are available on heart function in chronic testosterone deficiency and on the effect of estrogen treatment. Eighteen 4-week-old male Lewis rats were randomly divided into 3 groups (n = 6): 1 group of sham-operated rats and 2 groups of castrated rats. Sixty-six weeks after surgery, 1 castrated group received a dose of 17β-estradiol (10 μg/kg per day) and the remaining 2 groups received a placebo subcutaneously for 14 days. Left ventricular (LV) systolic and diastolic functions were measured by transthor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To asses left ventricular diastolic function, the diastolic transmitral peak early filling velocity (E velocity) and the diastolic transmitral peak late filling velocity (A velocity) were measured, and their ratio (E/A) was calculated from the two-dimensionally guided Doppler spectra of mitral inflow in apical four-chamber view. All measurements were averaged over three consecutive cardiac cycles [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…To asses left ventricular diastolic function, the diastolic transmitral peak early filling velocity (E velocity) and the diastolic transmitral peak late filling velocity (A velocity) were measured, and their ratio (E/A) was calculated from the two-dimensionally guided Doppler spectra of mitral inflow in apical four-chamber view. All measurements were averaged over three consecutive cardiac cycles [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although this study was done in female rats, estrogens have been shown to protect both female and male hearts from various stresses [40][41][42], even though the defense mechanisms involved might be different [43]. Indeed, it would be interesting to investigate rMCPs expression levels in cardiomyocytes from male rats and their corresponding roles in sexspecific cardiac function and morphology.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Estrogen deprivation mitigated this cardioprotection [54][55][56][57] . On the other hand, estrogen reposition was able to increase cardiomyocytes' survival in a murine model of infarction, prevent hypertrophy in cardiomyocytes' culture, and improve cardiac function in the isolated hearts of gonadectomized rats 58,59 . According to literature, the activation of membrane-bound receptor G proteincoupled estrogen receptor (GPER) and estrogen receptor beta (ERβ) modulates Ca 2þ homeostasis.…”
Section: Discussionmentioning
confidence: 98%